Determinants of tax evasion: A systematic literature review - Niken Safitri; Muhammad Zaky (WIM Solusi Prima, 2026)
Tax evasion is a serious fiscal problem with wide-ranging effects on state revenue, the fairness of the tax system, and the effectiveness of public policy across countries, particularly developing countries. This study aims to identify, evaluate, and synthesize empirical evidence on the determinants of tax evasion globally through a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. The literature search was conducted in the Scopus database using the keyword “tax evasion,” covering publications from 2016 to 2026. After a staged selection process, 32 scientific articles meeting the inclusion criteria were systematically analyzed. The results show that the determinants of tax evasion are multidimensional and can be grouped into three main paradigms: the deterrence paradigm, which covers tax rates, audit probability, and sanctions; the service-trust paradigm, which covers the quality of public services, government legitimacy, and perceptions of fairness; and the fiscal psychology paradigm, which covers religiosity, social norms, tax morale, and loss aversion. Corruption is shown to be a destructive factor that consistently increases tax evasion, while religiosity and the quality of tax services are effective protective factors. This study also identifies research gaps related to the developing-country context, more specific dimensions of religiosity, and the spillover effects of corruption on tax compliance. These findings are expected to provide both theoretical contributions and practical implications for tax authorities and policymakers in designing more effective and sustainable strategies to improve tax compliance.